Smart Phone Technology for Diabetic Retinopathy Screening in a Rural Setting - Sarita RJ Lobo; Anjali Mohan; Geover Joslen Lobo (TNOA Journal of Ophthalmic Science and Research)
To compare the accuracy and reliability of a smartphone ophthalmoscope using an application I Examiner pro with that of a slit-lamp biomicroscope to grade diabetic retinopathy (DR) in patients with diabetes mellitus (DM). This is a prospective, hospital-based comparative study where 90 patients with diabetes mellitus between 40–70 years attending the ophthalmology outpatient department were evaluated over a period of 1 year. Smartphone ophthalmoscopy showed considerable agreement with slit-lamp biomicroscope for the grading of DR. The portability, affordability, and connectivity of smartphone ophthalmoscope make it a promising technique for community screening programs and early detection of diabetic retinopathy in the rural setup.